5S‐IGS rDNA in wind‐pollinated trees (Fagus L.) encapsulates 55 million years of reticulate evolution and hybrid origins of modern species. (29th November 2021) - Cardoni, Simone; Piredda, Roberta; Denk, Thomas; Grimm, Guido W.; Papageorgiou, Aristotelis C.; Schulze, Ernst‐Detlef; Scoppola, Anna; Salehi Shanjani, Parvin; Suyama, Yoshihisa; Tomaru, Nobuhiro; Worth, James R. P.; Cosimo Simeone, Marco
SUMMARY: Standard models of plant speciation assume strictly dichotomous genealogies in which a species, the ancestor, is replaced by two offspring species. The reality in wind‐pollinated trees with long evolutionary histories is more complex: species evolve from other species through isolation when genetic drift exceeds gene flow; lineage mixing can give rise to new species (hybrid taxa such as nothospecies and allopolyploids). The multi‐copy, potentially multi‐locus 5S rDNA is one of few gene regions conserving signal from dichotomous and reticulate evolutionary processes down to the level of intra‐genomic recombination. Therefore, it can provide unique insights into the dynamic speciation processes of lineages that diversified tens of millions of years ago. Here, we provide the first high‐throughput sequencing (HTS) of the 5S intergenic spacers (5S‐IGS) for a lineage of wind‐pollinated subtropical to temperate trees, the Fagus crenata – F. sylvatica s.l. lineage, and its distant relative F. japonica . The observed 4963 unique 5S‐IGS variants reflect a complex history of hybrid origins, lineage sorting, mixing via secondary gene flow, and intra‐genomic competition between two or more paralogous‐homoeologous 5S rDNA lineages. We show that modern species are genetic mosaics and represent a striking case of ongoing reticulate evolution during the past 55 million years. Significance Statement: The evolution of extra‐tropical wind‐pollinated tree genera involves dynamic speciation processes. High‐throughput sequencing of the multi‐copy, potentially multi‐locus 5S rDNA reveals a complex history of hybrid origins, lineage sorting and mixing, and intra‐genomic competition between paralogous‐homeologous loci in the core group of Eurasian beech trees (genus Fagus ) and their distant relative, F. japonica . The modern species are genetic mosaics and represent a striking case of at least 55 million years of ongoing reticulate evolution.